Isolation of actinomycetes from maize rhizosphere from Kupang, East Nusa Tenggara Province, and evaluation of their antibacterial, antifungal, and extracellular enzyme activity - Umi Fatmawati; Yulin Lestari; Anja Meryandini; Abdjad Asih Nawangsih; Aris Tri Wahyudi (Universitas Gadjah Mada, 2018)
Actinomycetes are the one of the components of the rhizospheric microbial population and useful for producing secondary metabolites such as lytic enzymes, antibiotics, and antifungal. The aim of the study was to isolate the actinomycetes from maize rhizosphere collected from Kupang, East Nusa Tenggara. The screening was focused on the actinomycetes that showed the ability to produce antibacterial, antifungal, and extracellular enzymes such as amylase, cellulase, and protease. The actinomycetes were isolated using Humic-Acid Vitamin B (HV) agar media. The antagonistic assay was tested against Escherichia coli, Staphylococcus aureus, Sclerotium rolfsii and Fusarium oxysporum. Isolate JKP-8 was an isolate that showed the highest activity in inhibiting the growth of E. coli and S. aureus bacteria. Isolate JKP-5 showed the highest activity in inhibiting the growth of F.oxysporum. There were no actinomycetes isolates that showed an ability to inhibit the growth of S. rolfsii fungus based on dual culture assay. JKP-3 and JKP-4 isolates exhibited the highest ability to hydrolyze amylum, while JKP-5 and JKP-8 isolates exhibited the highest ability to hydrolyze CMC. The results of the amplification of 16S rRNA gene in selected potential isolates JKP 5 and JKP 8 indicated that both isolates belong to the genus Streptomyces.